2014
DOI: 10.1016/j.biortech.2014.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of lignocellulosic hydrolyzate using a submerged membrane bioreactor at high dilution rates

Abstract: Please cite this article as: Ylitervo, P., Doyen, W., Taherzadeh, M.J., Fermentation of lignocellulosic hydrolyzate using a submerged membrane bioreactor at high dilution rates, Bioresource Technology (2014), doi: http:// dx.doi.org/10. 1016/j.biortech.2014.04.066 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For example, a medium containing 17.0 g/L furfural could be continuously fermented by using a membrane bioreactor to obtain cell densities of up to 180 g cell dry weight/L [45]. Furthermore, Ylitervo et al showed that continuous fermentation of spruce hydrolysate was possible at dilution rates of 0.8 h –1 in a submerged membrane bioreactor at cell densities of 60 g cell dry weight/L [46].…”
Section: Case Specific Benefits and Characteristics Of High Cell Dementioning
confidence: 99%
“…For example, a medium containing 17.0 g/L furfural could be continuously fermented by using a membrane bioreactor to obtain cell densities of up to 180 g cell dry weight/L [45]. Furthermore, Ylitervo et al showed that continuous fermentation of spruce hydrolysate was possible at dilution rates of 0.8 h –1 in a submerged membrane bioreactor at cell densities of 60 g cell dry weight/L [46].…”
Section: Case Specific Benefits and Characteristics Of High Cell Dementioning
confidence: 99%
“…The membrane completely retained the biomass, which then was partly recycled into the bioreactor to maintain a high biomass concentration, to operate at both high dilution and high growth rates. Ylitervo et al (2014) applied submerged MBR to enrich density of Saccharomyces cerevisiae for fermenting toxic lignocellulosic hydrolyzate to ethanol. The MBR demonstrated rapid and productive ethanol production from wood hydrolyzate.…”
Section: Revised Process Architecturementioning
confidence: 99%
“…Specific agricultural lignocellulosic waste substances such as rice straw and wheat straw (Ishola et al 2013, 2015a,b, Ylitervo et al 2014, Zahed et al 2016 have been mainly exploited in experimental studies of membrane reactor facilitated lignocellulosic bioethanol production process. In some experimental studies (Lee et al 2000, Ylitervo et al 2014, general lignocellulosic hydrolyzate materials were investigated in MBR-based bioethanol production process. Information related to specific lignocellulosic substrates used until now for MBR facilitated bioethanol production, maximum product concentration or productivity achieved, and membrane materials or modules used in those studies are represented in Table 2.…”
Section: Lignocellulosic Substrates For Membrane Technologybased Bioementioning
confidence: 99%
“…Another advantage of such membrane cell recycle fermentation system (MBR) is that the dilution rate is not dependent on the growth rate of the microorganism (Ylitervo et al 2013). High dilution rates lead to maximum bioethanol productivity and yields (Ylitervo et al 2014). Low dilution rates are the only possible operating conditions in which traditional continuous cultivation systems without cell recycle are successful (Brandberg et al 2008).…”
Section: Mbrs For Fermentative Production Of Lignocellulosic Bioethanolmentioning
confidence: 99%
See 1 more Smart Citation